DSP-Free Carrier Phase Recovery System for Laser-Forwarded Offset-QAM Coherent Optical Receivers - Rezaei, Marziyeh; Sturm, Daniel; Zeng, Pengyu; Moazeni, Sajjad (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
Co-packaged optics (CPO) are emerging as a promising solution to address future off-package I/O bandwidth scalability challenges. While previously proposed CPO solutions have primarily focused on pulse amplitude modulation (PAM), employing coherent modulation techniques could further enhance data rates. However, optical coherent transceivers often exhibit high power consumption and inefficient use of area. In this work, we propose a new DSP-free carrier phase recovery system for offset-QAM modulation based on a laser-forwarding technique. Offset-QAM can be realized with lower area and power optical modulators. The proposed approach is simulated and validated using Global Foundry monolithic 45nm silicon photonics PDK models with the circuit/system-level implementation at 25GBaud offset-QAM-4. This technique can also be extended to higher-order modulations such as QAM-16.